Student with Down syndrome in mainstream school? - Joanna Kruk-Lasocka; Bożena Bartosik; Anna Jakubowska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The article presents a level of  socio-emotional competences of children with Down Syndrome and with moderate learning difficulties in the period of early stage education. The aim of this article is to answer the question: ' How the student with Down syndrome would manage the education in the mainstream settings'? The competences, which 5 years old children typically developed reach, were measured. The research were conducted within 30 children with Down syndrome age 8 to 13. The results of the research shows low level of competences both emotional and social. The research was based on Inventory of Socio-Emotional Competences (IKES) created by J. Kruk-Lasocka and A. Szymajda. Introduction to the article is a theoretical analyze of other researchers who studied development of children with Down syndrome in contexts of their ability to follow educational program in mainstream education.